Prognosis and Clinical Results after Coronary Artery Bypass Operation in Young Patients Aged <45 Years: Chances and Limitations of a New Therapy Option - Wittlinger, Thomas; Schramm, René; Bleiziffer, Sabine; Rudolph, Volker; Gummert, Jan Fritz; Deutsch, Marcus-André (The Thoracic and Cardiovascular Surgeon, 2021)
Coronary artery bypass grafting (CABG) is the recommended type of revascularization procedure in patients with left main or three-vessel disease and is considered an alternative when percutaneous coronary intervention is not feasible. We evaluated registry data to obtain long-term outcome data.All patients ≤45 years in whom CABG was performed between 2009 and 2019 were selected from the Heart and Diabetes Center NRW, Germany. Cox regression analysis was applied to estimate the incidence risk of events after surgery.A total of 209 patients (81.8% male) were included. Mean (standard deviation) follow-up duration was 5.8 (3.1) years. The combined outcome of death, stroke, myocardial infarction, or repeated revascularization occurred in 31 patients (14.8%). Estimated mean time to event was 8.5 (standard error: 0.22) years. By the end of the follow-up period, 8 patients (3.8%) had died, among whom 2 (1.0%) died within 1 month after surgery, 1 (0.5%) within 1 year, 1 (0.5%) within 2 years, and 4 (1.9%) after 2 years.Risk factors independently associated with postsurgery events were angina pectoris CCS (Canadian Cardiovascular Society) class IV (adjusted hazard ratio [HR]: 4.954; 95% confidence interval [CI]: 1.322–18.563; p = 0.018) and STS (Society of Thoracic Surgeons) score (adjusted HR: 1.152 per scoring point; 95% CI: 1.040–1.276; p = 0.007).After performing CABG in patients ≤45 years, event-free long-term outcomes were observed in the majority of patients. Presence of angina pectoris CCS class IV and higher STS scores were independently associated with adverse postsurgery events.
Keywords: coronary artery bypass grafting; revascularization; angina pectoris; outcome